Analisis Persepsi Peserta Didik Terhadap Pembelajaran Daring Berbasis Video conference di Masa Pandemi Covid-19 - Fatmawati, Fatmawati; Namira, Hafifah; Busyairi, Ahmad (Mataram University, 2021)
During the covid-19 pandemic, most lecturers in higher education conduct the learning process with video conference. However, it seems that the use of video conferences in learning is believed to still be considered no more effective than face-to-face methods directly. Various perceptions related to the use of video conferences have sprung up from various circles. This research aims to find out the perception of students to the use of video conferences in the learning process in the pandemic period. The sample consisted of 49 students at one of the universities in Mataram City. The method used in this study is descriptive research methods. The data was retrieved using questionnaires and interviews. Based on the results of the data analysis showed that, as many as 86.39% of students have a positive perception of the use of video conferences in the learning process during the pandemic. The average student assumes that using video conferences can facilitate the learning process, can motivate students in learning, and more effective in communicating with lecturers when compared to using platforms that can only send messages in the form of text.